Emergent threats: lessons learnt from Ebola. Issue 5 (6th August 2019) - Piot, Peter; Soka, Moses J; Spencer, Julia
Abstract: Recent disease outbreaks have demonstrated the severe health, economic and political crises that epidemics can trigger. The rate of emergence of infectious diseases is accelerating and, with deepening globalisation, pathogens are increasingly mobile. Yet the 2014–2015 West African Ebola epidemic exposed major gaps in the world's capacity to prevent and respond to epidemics. In the midst of the world's second largest ever recorded Ebola outbreak in the Democratic Republic of the Congo, we reflect on six of the many lessons learnt from the epidemic in West Africa, focusing on progress made and the challenges ahead in preparing for future threats. While Ebola and other emerging epidemics will remain a challenge in the years to come, by working in partnership with affected communities and across sectors, and by investing in robust health systems, it is within our power to be better prepared when they strike.